CUSTOMER RELATIONSHIP MANAGEMENT INFLUENCE ON CUSTOMER VALUE, PRODUCT QUALITY AND SERVICE QUALITY IN IMPROVING CUSTOMER SATISFACTION AND ITS IMPLICATION ON THE CUSTOMER LOYALTY - Sri Harryani (Jurnal Ilmiah Ekonomi Bisnis, 2017)
The purpose of this research is to determine the influence of Customer Relationship Management (CRM) on the Customer Value (CV), Product Quality (PQ) and Service Quality (SQ) in improving Customer Satisfaction (CS) that will have implications on the Customer Loyalty (CL). The research focuses on corporate banking, where customers serve as the research sample. The data in this research using the primary data and secondary data. Source primary data used questionnaire and source the secondary data obtained from variety resources that have been published. By using a likert scale questionnaire with the respondent obtained as much as 360 customers. The analytical tool used in this research is Structural Equation Modelling (SEM) with AMOS version 6 program for testing hypotheses and software SPSS 18 for construct validity and reliability test.Based on the testing, all hypothesis can be accepted. This indicates that a good CRM will increase the CV, PQ and SQ, then the increasing ofCV,PQ and SQ will increase the level of satisfaction felt by the customer. Thus, Customer Loyalty is affected by Customer Relationship Management with intervention by Customer Value, Product Quality, Service Quality and Customer Satisfaction. Keywords: Customer Loyalty, Customer Satisfaction, Customer Relationship Management, Customer Value, Product Quality, Service Quality